Towards a New Era in the Management of Large Periapical Lesion in Permanent Tooth Using Stemcells: A 2-Year Clinical Application Report - Madu Ghana Shyam Prasad; Ramakrishna Juvva; Naveen Babu Duvvi (Shiraz University of Medical Sciences, 2019)
Stem cells are considered as the principal source of differentiated cells. In the past few years, the research on the stem cell in various fields had shown success, but the stem cell-based therapies in the dentistry had confined to a particular extent. The present case report was aimed to evaluate the efficacy of stem cells from human exfoliated deciduous teeth (SHED) in the management of a large periapical lesion. A 12-year-old girl reported with a chief complaint of pain in the lower right back tooth region since 5 days. Intraoral examination revealed a deep occlusal cavity in relation to tooth#46 with tenderness on percussion. Radiograph examination revealed periapical radiolucency measuring 1.8×1.0cm in size with perforation at the floor of the pulp chamber in relation to 46. A deciduous tooth from the same child was collected to isolate stem cells. After access opening for tooth #46, pulp was extirpated and a thick mucoperiosteal flap was raised. This was followed by homing of SHED into the periapical area through the window created in the buccal cortical plate and into the root canals of tooth #46 until the orifice. The access cavity was sealed with glass ionomer cement. The patient was subjected to evaluation at regular intervals i.e., two weeks, four months, twelve months, and twenty-four months. The case treated demonstrated complete resolution of periapical radiolucency in the fourth-month review with a positive response to electric pulp testing. This clinical application report concludes that SHED can be effective in treating the periapical lesions in permanent teeth.